RF-DC conversion for RF energy harvesting from digital TV signals using voltage multiplier circuits - Piyapat Panmuang; Amornthep Sonsilphong; Chaiyong Soemphol (Universitas Ahmad Dahlan, 2024)
Due to the development of wireless communications, there has been a growth in the use of IoT devices and sensor nodes. A potential power source for powering equipment in remote or inaccessible locations is necessary. This research investigates the feasibility of employing digital television (DTV) signals as an energy harvesting system, with a focus on RF-DC conversion using a voltage multiplier circuit. Commercial 5 and 9 element yagi-uda antennas are used as receiver for ambient DTV signal. The device’s performance is initially evaluated within the laboratory setting, it has been shown that when the RF signal generator is at 660 MHz, the proposed energy harvesting device can generate a maximum DC voltage of 781.3 mV and 1056.4 mV for 5 and 9 element antenna, respectively. This is based on measurement of voltage output when using the input signal from DTV base stations in Thailand. It was found that the voltage output levels decreased gradually with increasing distance ranging from 153.4 V at 0.1 km to 4.5 mV at 10 km for 5 element yagi-uda antenna. In contrast, the 9-element yagi-uda antenna consistently exhibited higher voltage levels, ranging from 354.7 mV at 0.1 km to 12.6 mV at 10 km.